2015
DOI: 10.1016/j.ijmultiphaseflow.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of solid elongated particles on the surface of a stationary gas bubble

Abstract: Froth flotation is a separation process which plays a major role in the mining industry. It is essentially employed to recover a vast array of different valuable commodities such as rare earth minerals essential to the manufacture of high-tech products. Owing to its simplicity, the process is also widely used for de-inking recycled paper fibres and for waste water treatment. The flotation process essentially relies on the attachment of solid particles on the surface gas bubbles immersed in water. The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…This tendency is in-line with the reference data. 27 The same evolution of the particle velocity is also shown in Figure 6(b) as a function of the polar angle and brings a more natural visualisation of the collision and sliding processes. The polar angle ranges from α ≈ 0…”
Section: -9mentioning
confidence: 57%
See 1 more Smart Citation
“…This tendency is in-line with the reference data. 27 The same evolution of the particle velocity is also shown in Figure 6(b) as a function of the polar angle and brings a more natural visualisation of the collision and sliding processes. The polar angle ranges from α ≈ 0…”
Section: -9mentioning
confidence: 57%
“…The data from the first reference were obtained from a particle-point model 3 and proved accurate in the simulation of finely attaching particles. 27 In the second comparative experiment, 28 the liquid was brought in slow laminar motion around a pinned gas bubble. Although the microspheres later detached after a temporary sliding, the experimental trajectories are suitable for comparison during the particle approach.…”
Section: B Particle Attachment (S4)mentioning
confidence: 99%
“…This observation result is similar to results found in previous works. Figures 9 and 10 show particle movement in experimental and numeric calculations from the 45° angle up to the 120° angle of the previous experiments by Wang et al (2015) and Lecrivain et al (2015).…”
Section: Resultsmentioning
confidence: 91%
“…Frames 4-7 show the bubble rising, the particle detaching, and the particle moving downward. result Figure 10 Illustration of bubble-spherical particles interaction, experimental result, and numerical result (Lecrivain et al, 2015) Sliding movements on the bubble surface have different velocity values. It was observed that after collision with the bubble surface at quadrant 1, the particle slides slowly, and it then accelerates when moving into quadrant 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation